The Investigation of the Impact of Good Corporate Governance on the Value of Manufacturing Companies Listed on the IDX - Ciptawan, Ciptawan; Andoko; Putra, Ali Syah; Yenni; Arifin (Indonesian Journal Economic Review (IJER), 2025)
This study aims to determine the effect of good corporate governance on company value (a study of manufacturing companies listed on the IDX in 2022-2024). The selection of this study used purposive sampling, so that the number of samples used was 41 companies from a population of 144 companies. In this study, the results of the analysis were carried out to draw conclusions about the effect of good corporate governance on company value (a study of manufacturing companies listed on the IDX in 2022-2024). Data processing using Eviews 12. The results of the study show that managerial ownership affects company value in Manufacturing Companies on the IDX in 2022-2024. Institutional ownership affects company value in Manufacturing Companies on the IDX in 2022-2024.